Adiponectin gene variants, adiponectin isoforms and cardiometabolic risk in type 2 diabetic patients. Issue 2 (2nd September 2013) - Foucan, Lydia; Maimaitiming, Suliya; Larifla, Laurent; Hedreville, Segho; Deloumeaux, Jacqueline; Joannes, Marie‐Odile; Blanchet‐Deverly, Anne; Velayoudom‐Céphise, Fritz‐Line; Aubert, Roberte; Salamon, Roger; Donnet, Jean‐Paul; Fumeron, Frederic
Abstract Aims/Introduction The aim of the present study was to examine the associations of rs2241766 (+45T>G), rs1501299 (+276G>T), rs17300539 (−11391G>A) and rs182052 (−10069G>A) in the adiponectin (Ad) gene with adiponectin concentrations, and concomitantly the association of these variants with cardiometabolic risk in type 2 diabetic patients of African ancestry. Materials and Methods A cross‐sectional study of 200 patients was carried out. Concentrations of total, high (HMW), middle (MMW) and low (LMW) molecular weight adiponectin isoforms were measured. The four polymorphisms were genotyped. Results Decreased values were noted for total Ad in overweight, dyslipidemia and coronary artery disease (CAD), for HMW in overweight and dyslipidemia, for MMW in CAD, for LMW in dyslipidemia and CAD, for the percentage HMW/total in overweight, and for MMW:HMW ratio in patients without hypertriglyceridemic waist (HTGW). Significant associations were noted between total Ad, HMW, and HMW/total Ad and rs182052 under a dominant model (P = 0.04, P = 0.03 and P = 0.04, respectively), and between MMW and rs17300539 (P = 0.006). No significant difference in adiponectin concentrations was noted according to rs2241766 and rs1501299 genotypes. Patients carrying the rs2241766 G allele (TG+GG) had an increased risk of HTGW (odds ratio [OR] 3.1; P = 0.04) and of CAD (OR 3.3; P = 0.01). The odds of having low total adiponectin concentrations (<25th percentile: 3.49 ng/mL) for carrying the rs182052A allele (AA+GA) was: OR 0.40; P = 0.009. The single‐nucleotide polymorphism associated with adiponectin levels was not concomitantly associated with cardiometabolic risk factors. Conclusions Adiponectin concentrations and ADIPOQ variants are implicated in the pathophysiological process leading to cardiovascular diseases, but the genetic effects seem to be independent of adiponectin concentrations in our Afro–Caribbean diabetic patients.